2021
DOI: 10.21203/rs.3.rs-312197/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimization of the Feeding rate of Anopheles Farauti Colony Mosquitoes in Direct Membrane Feeding Assays

Abstract: Background: Direct membrane feeding assays (DMFA) are an important tool to study parasite transmission to mosquitoes. Mosquito feeding rates in these artificial systems require optimization as there are a number of factors that potentially influence the feeding rates and there are no standardized methods that apply to all Anopheline species.Methods: A range of parameters prior to and during direct membrane feeding (DMF) were evaluated for their impact on Anopheles farauti feeding rates; including the starving … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…The experimental time for arm feeding was 1 h to allow for standardized evaluation and to minimize volunteer discomfort. Previous work has shown that 30 minutes of exposure resulted in high blood feeding (Timinao et al, 2021).…”
Section: Bait Used and Preparationmentioning
confidence: 93%
See 2 more Smart Citations
“…The experimental time for arm feeding was 1 h to allow for standardized evaluation and to minimize volunteer discomfort. Previous work has shown that 30 minutes of exposure resulted in high blood feeding (Timinao et al, 2021).…”
Section: Bait Used and Preparationmentioning
confidence: 93%
“…Membrane feeding has been widely deployed for evaluating topical mosquito repellents (Debboun, 2004), transmission-blocking drugs and vaccines (Vallejo, et al, 2016), endoctocides (Smit, 2018) as well as for mosquito rearing (Awono- Damiens, 2013;Kaufman, 2014;Phasomkusolsil et al, 2013;Robert, 1998;Timinao et al, 2021). Moreover, the use of an artificial membrane has several advantages including reduced animal welfare or ethical concerns, reduced chance of accidental disease transmission, simple logistics, and reproducibility Kaufman, 2014;Phasomkusolsil et al, 2013;Timinao et al, 2021). Given the significance of host kairomones to encourage mosquito feeding, worn socks added to augment the attractiveness of the membrane to mosquitoes (Pates et al, 2001) during host seeking process.…”
Section: Muhtasari (Abstract)mentioning
confidence: 99%
See 1 more Smart Citation